Riffatere’s Semiotic on Simon Armitage’s Out of the Blue (2014) Poem - Santosa, Budi Tri; Rachmatika, Neni Virginia; Hardiyanti, Diana (Lingual Journal of Language and Culture, 2024)
This research aims to find out the explicit meaning of the poem Out of The Blue which is analyzed using Riffaterre's Semiotic theory, which according to Riffaterre, poetry is a sign system that needs to be interpreted further. According to Riffaterre, the meaning of poetry is divided into four stages. First, indirectness of expression in the form of changing meaning in the form of metaphor, simile, personification, metonymy, deviation of meaning in the form of ambiguity, contradiction and nonsense, to the creation of meaning in the form of rhyme, symmetry and homology. Heuristic reading to find linguistic meaning. Hermeneutic reading to clarify the meaning of poetry. Then find matrices, models and variants to find keywords contained in the poetry. Finally, a hypnogram to find out the background to the creation of the poem Out of The Blue. The research method used in this research is a qualitative descriptive method to describe and interpret the data studied. The data in this research are primary and secondary data. The primary data in this research are lines in the poem Out of The Blue. Meanwhile, for secondary data, researchers used Riffaterre's Semiotics theory, journals for writing scientific papers, and books related to literary works. The results of this research show that the poem Out of The Blue describes the suffering of New Yorkers in the form of a struggle to survive when terrorists attack, which is implied through certain verses. The terrorist attacks in America caused great traumatic feelings, including the loss of loved ones, deep sadness, depression, hopelessness, and even material and immaterial losses.